2018
DOI: 10.1007/s00404-018-4942-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with misoprostol vaginal insert for induction of labor: a prospective clinical observational study

Abstract: PurposeTo provide real-world evidence using misoprostol vaginal insert (MVI) for induction of labor in nulliparous and parous women at two German Level I Centers in a prospective observational study.MethodsBetween 1 August 2014 and 1 October 2015, eligible pregnant women (≥ 36 + 0 weeks of gestation) requiring labor induction were treated with MVI. Endpoints included time to and mode of delivery rates of tocolysis use, tachysystole, uterine hypertonus or uterine hyperstimulation syndrome and newborn outcomes.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
2
8
1
3
Order By: Relevance
“…Our re-sults, however, showed different dynamics of the action of two compared drugs. Misoprostol has shown greater effectiveness compared to dinoprostone, which is consistent with studies by other authors [16][17][18]. Its higher efficiency is manifested by a significant shortening of the delivery time, both in the first and the second stage of labor [18].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our re-sults, however, showed different dynamics of the action of two compared drugs. Misoprostol has shown greater effectiveness compared to dinoprostone, which is consistent with studies by other authors [16][17][18]. Its higher efficiency is manifested by a significant shortening of the delivery time, both in the first and the second stage of labor [18].…”
Section: Discussionsupporting
confidence: 88%
“…In our studies, the mean time from vPG administration to the onset of labour differed significantly between primiparous and multiparous women. In the studies by Shmid et al [17], similar statistically significant relationships were obtained: 14.9 hours of primiparous women and 11.8 hours of multiparous women. According to the research literature, the use of dinorpostone compared to misoprostol is more often associated with the need to stimulate uterine contractions with oxytocin [16,20,21], although some authors report no significant differences between these two prostaglandins use [22].…”
Section: Discussionmentioning
confidence: 54%
“…The misoprostol slow-release vaginal insert has been assessed in five previous studies, also including multiparous women, that found consistent results compared with ours. Time from induction to delivery has been reported between 14.5-26.6 h and rates for CS was 7.5-40.1 [17][18][19][20][21][22][23]. Frequency of hyperstimulation was reported between 4.0 and 48.1%, leading to a higher CS rate and negative effects on neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins have been proven to induce labor whilst not increasing the rate of cesarean sections (CS) among women with unscarred uterus [7]. [8][9][10][11][12][13] even for women with an unfavourable cervix as to BISHOP scores [14], while reducing the need for oxytocin compared to dinoprostone vaginal insert or oral misoprostol [8,10,15].…”
Section: Resultsmentioning
confidence: 99%
“…Hyperstimulation syndrome requiring tocolysis is more common in women receiving MVI [8,10,11,14,16].…”
Section: Resultsmentioning
confidence: 99%